Partisipasi Anggota Pada Koperasi Simpan Pinjam (Ksp) Hati Nurani Desa Tambusai Barat Kecamatan Tambusai Kabupaten Rokan Hulu - Jubayanti '; Rosnita '; Jum'atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the level participation of member as owner and determine the level participation of member as client or consumer. This research using survey method. The sample determineusing bysimple random sampling. Analysed data were descriptive with using Likert’s Summated Rating Scale.The results of research provided that participation level of members as owner reside in medium category, which mean the members ofcooperatives saving and loan Hati Nurani have enough participate in taking decision, in capital contribution and in cooperation observation. The participation of members as client or consumer reside in high category, because the members have actived participate in exploitingservices which provide bycooperation. The participation of members in decision making, shall attendance members in meeting of members annual and in given suggestion or criticism shall more improve in order to help the foster growth of cooperation. Participation in cooperation observation shall more improve through a members involvement although in cooperation had formed supervisor team. Keywords: participation,saving and loan cooperatives, scale likert’s